MODERASI ISLAM: MEMBENTUK IDEALITAS PEMAHAMAN KEAGAMAAN ANTAR SESAMA UMAT ISLAM DALAM DUNIA PENDIDIKAN - Sayid Ahmad Ramadhan (CV. ADIBA AISHA AMIRA, 2025)
This study stems from the urgency to integrate Islamic Religious Education (PAI) with the values of religious moderation in an effort to cultivate a peaceful, open-minded, and reflective understanding of religion, particularly within educational settings. Using a library research method, this study not only examines the normative aspects of Islamic teachings but also explores pedagogical approaches that are contextual and relevant to the socio-cultural realities of students. Islamic moderation is positioned as a foundational paradigm for developing an inclusive, just, and balanced model of religious education that can respond to the challenges of internal diversity within the Muslim community. In this regard, PAI must be developed progressively through participatory and reflective approaches, placing students as active agents in critically understanding and internalizing religious values. The role of teachers is crucial as agents of value transformation, not only delivering Islamic content but also instilling a spirit of moderation that is applicable in daily life. Therefore, there is a need for a curriculum design and learning strategy that is integrative, adaptive, and rooted in the values of moderation, so that PAI can meaningfully contribute to shaping tolerant Muslim characters who are open-minded and capable of living harmoniously in a pluralistic society. The implications of this study indicate that strengthening Islamic moderation through education is a strategic step in sustaining inclusive and peaceful religious life amid an increasingly complex social landscape.